RELEVANSI KEMANDIRIAN HIDUP NAOMI DAN RUT TERHADAP KEHIDUPAN PEREMPUAN TORAJA - Mariance, Mariance; Salewa, Wandrio (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
In Toraja society, women tend to be seen as unable to survive without a man. This study wants to explore the story of Ruth and Naomi based on the book of Ruth, who lost her husband but survived and fought for a better future in a patriarchal society. Based on this story, the writer wants to contextualize it by using a praxis model in the lives of Toraja women. The research method used is qualitative with a literature study approach. The results show that: 1) women can make the best decisions for their families and face the risks; 2) women can be responsible for their families; 3) women can formulate effective plans and strategies for a better family future. The lives of Naomi and Ruth provide a theological message that Toraja women who still live in a patriarchal culture can also live like them. Toraja women can live independently, lead families, and ultimately contribute to wider life in society.